MODERATE YOUTH PROGRAM: SHAPING FUTURE GENERATIONS OF LEADERS WHO RESPECT DIVERSITY AND RELIGIOUS TOLERANCE - Muhammad Wandisyah R Hutagalung; Nurintan Muliani Harahap; Siti Wahyuni Siregar (RADJA PUBLIKA, 2026)
This community service program, titled